2011
DOI: 10.1590/s0100-29452011005000080
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade de abacaxizeiro cv. Smooth Cayenne, cultivado comaplicação de doses e parcelamentos do nitrogênio, em Guaraçaí-SP

Abstract: de N, e quatro parcelamentos: toda a dose aplicada antes da indução floral, metade da dose antes da indução floral e a outra metade após a indução, 2/3 da dose antes da indução e 1/3 da dose após a indução e toda a dose após a indução floral. A aplicação total do N após a indução floral, independentemente da dose, resultou em menores teores foliares de N e dimensões da folha "D", apresentando na colheita frutos pequenos, com menor índice de maturação e maior acidez. Para obtenção de frutos de abacaxi cv. Smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…After the initial growth period, plant growth characteristics (plant height, stem diameter, D-leaf length and mass) and fresh and dry biomass production of different plant components (leaves, stem, root) increased significantly, followed by the flower induction process at the end of stage V5 (approximately 630 DAP), with a subsequent stabilization in vegetative growth. These results are in accordance with the findings by Marques et al (2011), who reported that the vegetative growth of pineapple plants is drastically reduced after flowering/fructification when the plant's metabolism is directed to fruit development. These observations are common knowledge and serve as a basis for determining the phenological stages of pineapple plants (FOURNIER et al, 2010;RODRIGUES et al, 2010;SAMPAIO et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…After the initial growth period, plant growth characteristics (plant height, stem diameter, D-leaf length and mass) and fresh and dry biomass production of different plant components (leaves, stem, root) increased significantly, followed by the flower induction process at the end of stage V5 (approximately 630 DAP), with a subsequent stabilization in vegetative growth. These results are in accordance with the findings by Marques et al (2011), who reported that the vegetative growth of pineapple plants is drastically reduced after flowering/fructification when the plant's metabolism is directed to fruit development. These observations are common knowledge and serve as a basis for determining the phenological stages of pineapple plants (FOURNIER et al, 2010;RODRIGUES et al, 2010;SAMPAIO et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…The length and/or the fresh mass of leaf D in pineapple are considered reference estimates to define the moment of floral induction, as it generally presents a positive correlation with the mass and length of the infructescence at harvest (Rodrigues et al, 2010;Marques et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, in pineapple, the length and fresh mass of leaf D have been used as parameters to estimate plant maturity and productivity in cultivars already established in the market, such as 'Pérola' and 'Smooth Cayenne' (Rodrigues et al, 2010;Marques et al, 2011). Vilela et al (2015) recommends doing the floral induction in cv.…”
Section: Introductionmentioning
confidence: 99%
“…Type and doses of fertilizer applied and the timing of application influence the internal and external quality of pineapple fruits (COELHO et al, 2007;GUARÇONI & VENTURA, 2011;MARQUES et al, 2011, OLIVEIRA et al, 2015. According to COELHO et al (2007), the average fruit weight of the 'Jupi' pineapple was significantly higher at a dose of 93 g of NPK (20:05:20) plant -1 while the use of higher doses increased the contents of soluble solids and titratable acidity and reduced the soluble solids/ titratable acidity ratio.…”
Section: Introductionmentioning
confidence: 99%